Educating the 21st Century Language Teacher - Basol, Hasan Caglar; Inozu, Julide (Alberta Journal of Educational Research, 2019)
This study engages with how prospective teachers of English (PTEs) conceptualize intercultural communicative competence (ICC). In particular, we focus on the underlying sources that influence the development of ICC for pre-service teachers in a teacher education program in Turkey. A self-assessment scale and semi-structured interviews were used as data collection tools. The results reveal that the definition of ICC is vague among the PTEs, and their understanding of it is insufficient. In particular, while they can provide a definition of ICC, they rarely mention characteristics beyond linguistic competence. Further to this, travel and exchange programs, as well as peer interactions are the primary sources of ICC as reported by PTEs; while academic courses have no statistically significant contribution. Keywords: intercultural communicative competence; prospective teachers of English; perception; contributing sources; academic program Cette étude porte sur la façon dont les futurs enseignants d’anglais conçoivent la compétence communicative interculturelle (CCI). Plus particulièrement, nous nous penchons sur les sources sous-jacentes qui influencent le développement de la CCI chez les enseignants en formation dans un programme de formation à l’enseignement en Turquie. Une grille d’autoévaluation et des entrevues semi-structurées ont servi d’outils de collecte de données. Les résultats indiquent que la définition de la CCI est vague chez les futurs enseignants d’anglais et qu’ils possèdent insuffisamment de connaissances à ce sujet. Notamment, même s’ils sont en mesure de fournir une définition de la CCI, ils en notent rarement les caractéristiques autres que la compétence linguistique. De plus, comme sources principales de CCI, les futurs enseignants d’anglais nomment les voyages, les programmes d’échange et les interactions avec les pairs; les cours académiques n’y contribuent pas de façon statistiquement significative. Mots clés : compétence communicative interculturelle; futurs enseignants d’anglais; perception; sources contributrices; programme académique